KETERKAITAN LITERASI KEUANGAN PETAMBAK GARAM RAKYAT DENGAN PRODUKTIVITAS GARAM, MODAL, HARGA DAN AKSES PASAR - Didin SE. Fatihudin; Musriha .; Wiwi Wikanta; Hammadi Fauzi; Nurul Maulidiah; Iis Holisin; M. A. Firmansyah; Ikbar Luqyana; N. Evi Kartika (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2022)
This research is to analyze the linkage of financial literacy of salt farmers to people's salt production with land, volume, capital sources, market access. Financial literacy is the ability of farmers in understanding various types of financial products/services from the financial industry and able to use. The production of people's salt business (Kugar) has an important contribution to indonesia's national salt production. The quality of people's salt has not been able to meet domestic demand, especially industrial salt. That's what drives salt imports. Research object 7(seven)locations in Cirebon-West Java. Kapetakan, Suranenggala, Gunungjati, Mundu, Losari, Pangenan and Gebang. This region was chosen because it represents the highest salt products in West Java. Descriptive methods, expalanatory, pusposive sampling techniques. Interview and using secondary data from the Marine and Fisheries Service, Central Bureau of Statistics, people's salt business group (kugar), Ministry of Industry and Trade. The results of the study; Financial literacy is still very low. Productivity is also low. 2019 highest disposable salt production 136,695ton, down 2020 only 2,670.78ton. Production costs borrowed by financiers (collectors) from Rp500,000 to Rp1,000,000 with a revenue sharing system. The selling price of salt from farmers to financiers is below the market price between Rp250/kg, Rp300/kg is the highest Rp500/kg. Price of salt from financier to industry Rp1,200/kg, Rp1,500/kg to Rp2,000/kg. Price, market access and capital, salt farmers depend on financiers. Weak financial literacy understanding. The profit of salt is enough for the cost of living. Limited asset deposits in gold, cows, motorcycles. 74 percent of workers. It doesn't have a financial services product. Only know the cooperative and the loan from the collector.